2002
DOI: 10.2337/diabetes.51.4.1035
|View full text |Cite
|
Sign up to set email alerts
|

Human Obesity and Type 2 Diabetes Are Associated With Alterations in SREBP1 Isoform Expression That Are Reproduced Ex Vivo by Tumor Necrosis Factor-α

Abstract: Sterol regulatory element binding protein (SREBP)-1 is a transcription factor with important roles in the control of fatty acid metabolism and adipogenesis. Little information is available regarding the expression of this molecule in human health or disease. Exposure of isolated human adipocytes to insulin enhanced SREBP1 gene expression and promoted its proteolytic cleavage to the active form. Furthermore, 3 h of in vivo hyperinsulinemia also significantly increased SREBP1 gene expression in human skeletal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 36 publications
10
108
0
1
Order By: Relevance
“…Work in our lab has shown that in human WAT, the majority of SREBP1 expressed is in the SREBP1c isoform. 35 In addition, SREBP1c expression is higher in human mature adipocytes than in both undifferentiated and differentiated primary adipocytes. This suggests that mature adipocytes are the component of the WAT in which SREBP1c is likely to have its greatest effects.…”
Section: Srebp1c a Gatekeeper For Lipotoxicitymentioning
confidence: 98%
See 3 more Smart Citations
“…Work in our lab has shown that in human WAT, the majority of SREBP1 expressed is in the SREBP1c isoform. 35 In addition, SREBP1c expression is higher in human mature adipocytes than in both undifferentiated and differentiated primary adipocytes. This suggests that mature adipocytes are the component of the WAT in which SREBP1c is likely to have its greatest effects.…”
Section: Srebp1c a Gatekeeper For Lipotoxicitymentioning
confidence: 98%
“…The decrease in SREBP1 mRNA can be reproduced in human primary adipocyte cultures using TNFa. 35 Treatment for 24 h specifically decreases SREBP1c mRNA and can block the effect of insulin on mature SREBP1 protein. Interestingly, more recent work has shown that the inhibitory effect of TNFa on insulin-stimulated increases of mature SREBP1 protein can be reproduced in rat primary adipocyte culture model and is reproduced by C2-ceramide (Lelliott and Vidal-Puig, unpublished data).…”
Section: Srebp1c a Gatekeeper For Lipotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is now evidence both in humans and in rodents that SREBP-1c mediates insulin upregulation of genes encoding glycolytic and lipogenic enzymes in skeletal muscle, [42][43][44][45][46] but most fascinating are the very recent demonstrations that glucose alone (in the absence of insulin) can stimulate de novo lipogenesis in skeletal muscle cells. The evidence can be summarized as follows:…”
Section: Stimulatory Effects Of Glucose On Muscle De Novo Lipogenesismentioning
confidence: 99%